18 An audit of ct-coronary angiography use and results from the chest pain assessment unit 2016, connolly hospital, blanchardstown. (5th October 2017) - Brandon, L; Maleady, K; Broughall, M; Galvin, J; O'Neill, J
Abstract : Background: Major developments are ongoing in cardiology for the diagnosis of coronary artery disease, beyond ECG exercise stress test and invasive angiography. Options now include computed tomography coronary angiography (CTCA), cardiac MRI, stress echocardiography, and nuclear scintigraphy. Their proper utilisation has yet to be fully evaluated and depends on local experience, reflected by discrepencies between American and European guidelines. Aims: To evaluate the use of CTCA in Connolly Hospital Blanchardstown from the 1st January-31st December 2016, by reviewing patient profile referred including HEART Score, risk factors and results of investigations, with correlation to CTCA results. Methods: Review referral letters from CPAU requesting CTCA, alongside CTCA result and outpatient letters. Results: There were 196 patients referred for CTCA of 1117 assessed, 101 (51.5%) female, 95 male (48.5%), average age 53.9 years (range 34–75 years). The average HEART score was 2.8, with 2.5 risk factors per patient. From CTCA results, 106 showed normal coronary arteries (54%) and 33 showed minor disease (16.8%), of which 88 (63.3%) were female, 51 male (36.6%), 28 had positive ESTs (20.1%), and 45 had typical angina (32%). The average Heart Score was 2.6. Scattered non-obstructive disease recommending aggressive medical management was reported in 18. There were 35 CTCA reports (17.8%) recommending invasive angiograghy, 27 (77.1%) males and 8 (22.9%) females, with an average Heart Score of 3.2, and 3.19 risk factors. Typical angina was noted in 14, (38.8%) and 8 had positive ESTs (22.2%). One patient was admitted with ACS while awaiting CTCA. There were 3 non-attendances for appointment. Conclusion: There were 17.8% positive reports recommending invasive assessment and 9.18% showing moderate disease, correlating with higher Heart Scores. There were benign findings in 70.9%, the majority being female with lower Heart Scores and less risk factors. All Heart Scores of 0 and 1 had normal results, suggesting stricter referral of patients with Heart Scores > 2 may be considered.